Some indicators of productivity of Galshar red goat - D, Batsuren; B, Narantuya (Mongolian Journal of Agricultural Sciences, 2018)
The indigenous has reached 119.3 thousand heads in 2017 in Khentii province Galshar sum, an increase of 8.9 percent annually. The live weight of the spring for red goats of Galshar was the adult buck averages 48.5kg, young buck 28.07kg, adult doe 37.7kg, young doe 21.7kg, and spring weight is being increased until autumn, such as adult buck 29.3%, young buck 30.7%, adult doe 20.4%, young doe 47.7%. Cashmere yield of adult buck averages at 585.4g, 16.42mkm diameter, 4.54cm length, in the above sequence young buck 438.5; 15,84; 3.99; adult doe 492.2; 16.33; 4.52; young doe 411.4; 15.66; 3.86; Galshar red goat in slaughter rate is castrated adult male 52.6%, adult doe 52.3%, dairy milk yield the period of calving 154.6g, and 256.9 g of milk during peak dairy production and 13.9-17.4 milk of average lactation period. Галшарын улаан ямааны ашиг шимийн зарим үзүүлэлтүүд Хураангуй: Хэнтий аймгийн Галшар суманд үржүүлж буй нутгийн ямаа 2017 онд 119.3 мянган толгойд хүрсэн бөгөөд жилд дунджаар 8.9 хувиар өсчээ. Галшарын улаан ямааны бүдүүн ухны хаврын амьдын жин 48.5, борлон ухна 28.07, эм ямаа 37.7, охин борлон 21.7 кг ба хаврын жингээ намарт бүдүүн ухна 29.3%, борлон ухна 30.7%, бүдүүн эм ямаа 20.4 %, охин борлон 47.5% нэмэгдүүлдэг. Бүдүүн ухны ноолуурын гарц 585.4 г, голч 16.42 мкм, урт 4.54 см, дээрхи дараалаар борлон ухных 438.5; 15.84; 3.99; эм ямааных 492.2; 16.33; 4.52; охин борлонгийнх 411.4; 15.66; 3.86; байв. Галшарын улаан ямааны нядлагын гарц эр ямаанд 52.6%, эм ямаанд 52.3%, сүүний гарц төллөх үед 154.6 г, саалийн ид оргил үед 256.9 г сүү өгдөг ба саалийн хугацааны дунджаар 13.9-17.4 сүү ашигладаг. Түлхүүр үг: Галшар, ямаа, ноолуур, сүү, сааль